Montoneras andinas, violencia ritual y saqueos: el caso de los rebeldes de Huánuco (1811-1812) - Bazán Díaz, Marissa (2020)
The main objective of this work is to analyze the performance of the Andean mountains, which in 1812, managed to install a government junta in Huánuco. The violent actions in this rebellion not only meant disorder and barbarism, but they also had a symbolic role, which came from a ritual rationality, expressed mainly through looting. Without ignoring the role that the Creole armies had in the process of American independence, this approach makes it possible to make visible the active participation and indigenous leadership during the regional phase of that process, towards the construction of the new States.